2015
DOI: 10.1016/j.jiph.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of catastrophic health expenditures for households: An example of medical attention for the treatment of severe childhood malaria in Kinshasa reference hospitals, Democratic Republic of Congo

Abstract: This study aimed to estimate the incidence of catastrophic health expenditures faced by households in Kinshasa with children affected by severe malaria. A total of 1350 children below the age of 15 year who were hospitalized due to severe malaria were included in the study. We analyzed the incidence of households facing catastrophic expenditures according to two thresholds: 40% of the household's capacity to pay and 10% of the household's total consumption. Based on the '40% of the capacity to pay' threshold, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
2
18
0
2
Order By: Relevance
“…Our findings are consistent with the results of other studies reporting that the risk of catastrophic health expenditures was strongly associated with the type of hospitals that patients have access to utilization of healthcare [29]. Our results are consistent with similar findings from another study that showed that the burden of OOP payments was highest among the poor [30], but a high incidence of catastrophic health expenditures has also been found among poor income households [31]. This may reflect the severity of disease in the poor (low-income) groups, which may be greater than in the high-income groups.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with the results of other studies reporting that the risk of catastrophic health expenditures was strongly associated with the type of hospitals that patients have access to utilization of healthcare [29]. Our results are consistent with similar findings from another study that showed that the burden of OOP payments was highest among the poor [30], but a high incidence of catastrophic health expenditures has also been found among poor income households [31]. This may reflect the severity of disease in the poor (low-income) groups, which may be greater than in the high-income groups.…”
Section: Discussionsupporting
confidence: 93%
“…Inpatient HIV patients in Nigeria had the highest incidence of CHE (100%) at 10% household expenditure, while at 40% non-food expenditure, the incidence was reduced to 94.3% [ 38 ]. There was a high incidence of CHE at 40% non-food expenditure in the Democratic republic of Congo amongst hospitalised children with severe malaria which was at 81.1% capacity to pay [ 39 ]. Both studies with a high incidence targeted specific groups of patients and thus were not national representative surveys.…”
Section: Resultsmentioning
confidence: 99%
“…Households’ income level is the most consistent determinant of catastrophic health expenditure with higher-income groups being less likely to incur CHE relative to middle income- and lower-income groups [ 39 , 43 , 44 ]. This is also observed amongst HIV/ART related studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper has three main aims: first, to provide a debate on the potential of social protection contribution to addressing health insecurity, poverty, and vulnerability brought by healthcare expenditure in low-income countries. [19][20][21] Second, to explore the gaps in current and proposed social protection measures in healthcare, and third, to provide suggestions on how social protection intervention aimed at addressing health insecurity, poverty, and vulnerability may be effectively implemented. Unlike a standard and structured review paper, in this paper we adopted the approach in debate articles, where a convenience sample of the literature is reviewed and cited accordingly to inform the debate.…”
Section: Introductionmentioning
confidence: 99%